Valuing Architecture: Taste, Aesthetics and the Cultural Mediation of Architecture Through Television. Issue 3 (1st September 2014) - Stead, Naomi; Richards, Morgan
Abstract : In this paper we examine how architecture has been mediated and framed by two television documentary series: Civilisation: A Personal View by Kenneth Clark (1969) and Grand Designs (1999–present). Both are examples of 'authored documentary', and both also attempt the education of public taste: in Civilisation through the structured admiration of great civic buildings framed as monumental art, and in Grand Designs through desirable domestic buildings framed as instruments for the art of living. In the paper we examine how the series can be both linked and distinguished through practices of valuation.